DETERMINANTS OF STUDENTS INTEREST IN PURSUING PROFESSIONAL CERTIFICATIONS IN ACCOUNTING - Rikawati Rikawati; Vita Arumsari (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2020)
This study aims to obtain empirical evidence regarding personality, labor market considerations, professional recognition, financial appreciation and work environment on student interest in taking professional certification in accounting. It uses multiple linear regression analysis with the IBM SPSS (Statistical Package for Social Sciencess) program for Windows version 25. There are 250 respondents in this study from various university in Indonesia. The test results show that personality, job market considerations, professional recognition, financial rewards have an effect on student interest in taking professional certification in accounting, while the work environment does not affect student interest in taking professional certification in accounting.